Ultra-low energy processing of graphite: a fast-track journey towards carbon neutrality. (December 2022) - Dai, Zhiquan; Cong, Lulu; Zuo, Fei; Biesuz, Mattia; Chen, Kan; Bertolotti, Mauro; Kermani, Milad; Yong, Lin; Tyrpekl, Václav; Hu, Chunfeng; Boi, Filippo; Lin, Hua-Tay; et al.
Highlights: -An environmentally friendly route to consolidate graphite at room temperature. -The cold pressed graphite in plane thermal conductivity as high as 620 W/m·K. -The room temperature compaction retained the rhombohedral phase. -The resulting products were fully recyclable for several times. Abstract: Graphite is a fascinating material with unique properties, thus making it irreplaceable for a wide range of applications. However, its current processing route is highly energy demanding as it requires dwelling for several hours at high temperatures (2500-3000°C). We report on the near full consolidation (relative density greater than 95%) at room temperature of graphite flakes under a mild uniaxial or isostatic pressure (100-500 MPa). The application of an external pressure promoted the formation of van der Walls bonds between the flakes, and the consolidation (pore removal) was mostly achieved by interplanar slipping. Despite the room temperature processing, with embodied energy below 1 MJ/kg, the resulting compact had in plane electrical and thermal conductivities as high as 0.77 × 10 6 S/m and 620 W/m·K (exceeding commercial isotropic graphite ≈0.09 × 10 6 S/m and 120 W/m·K). The bulks were thermally stable up to 1800°C. Because of the reversible nature on the van der Walls bonding, the cold pressed pellets were fully recyclable (i.e., easily milled and re-shaped) with a mild degradation of the electrical conductivity from 0.77 to 0.19 × 10 6 S/m after ten cycles. Graphical abstract: Image, graphical abstract